2023
DOI: 10.1038/s41534-023-00712-w
|View full text |Cite
|
Sign up to set email alerts
|

Observation of critical phase transition in a generalized Aubry-André-Harper model with superconducting circuits

Abstract: Quantum simulation enables study of many-body systems in non-equilibrium by mapping to a controllable quantum system, providing a powerful tool for computational intractable problems. Here, using a programmable quantum processor with a chain of 10 superconducting qubits interacted through tunable couplers, we simulate the one-dimensional generalized Aubry-André-Harper model for three different phases, i.e., extended, localized and critical phases. The properties of phase transitions and many-body dynamics are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 54 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Apart from topological perspective, many studies have already shown rich nonequilibrium properties in the quasi-periodic AAH models, such as Anderson localization [52,58], mobility edge [59][60][61], multi-fractal states [62,63]. Up to now, the AAH model has been realized in various experiment platforms, such as ultracold atoms [58,64], photonic waveguides [4,18,65] and superconducting circuits [63].…”
Section: Bose-hubbard Model With Modulated Interactionmentioning
confidence: 99%
“…Apart from topological perspective, many studies have already shown rich nonequilibrium properties in the quasi-periodic AAH models, such as Anderson localization [52,58], mobility edge [59][60][61], multi-fractal states [62,63]. Up to now, the AAH model has been realized in various experiment platforms, such as ultracold atoms [58,64], photonic waveguides [4,18,65] and superconducting circuits [63].…”
Section: Bose-hubbard Model With Modulated Interactionmentioning
confidence: 99%
“…Dynamical signature of HSF via participation entropy.-As discussed above, the Hilbert space tends to fragment into many disconnected Krylov subspaces with different dimensions in Stark systems. A direct quantity reflecting the extent to which a time-evolved state |ψ(t)⟩ spreads over the Hilbert space [34,49] is the dynamical PE, defined as…”
mentioning
confidence: 99%